Cross-linkable random copolymers as dielectrics for low-voltage organic field-effect transistors. Issue 35 (21st September 2015) - Reis Simas, E.; Kang, E. S. H.; Gassmann, A.; Katholing, E.; Janietz, S.; von Seggern, H.
<x xml:space="preserve">Abstract</x> A novel co- and terpolymer utilizing cross-linkable azide groups has been proven to be applicable as thin-film dielectric in organic field effect transistors. Reliable operation with saturation currents above Vg = 4 to 5 V can be achieved for a dielectric thickness of smaller than 100 nm.